Effect of an Er,Cr:YSGG Laser on the Surface of Implants: A Descriptive Comparative Study of 3 Different Tips and Pulse Energies - Ehsan Chegeni; Antonio España-Tost; Rui Figueiredo; Eduard Valmaseda-Castellón; Josep Arnabat-Domínguez (MDPI AG, 2020)
Peri-implant diseases are one of the main complications of dental implants. There are no well-established guidelines regarding laser parameters for implant decontamination. The aim was to compare two different settings of irradiation of the Er,Cr:YSGG laser on dental implants regarding surface alterations and determine the best settings for less damage on the surface. An in vitro study was performed and 30 areas of dental implants were irradiated with two different regimes of energy per pulse 50 and 84 mJ (1.5 W/30 Hz and 2.5 W/30 Hz). A total of 30 sites of implants were irradiated with three different tips (10 surfaces per tip): conical (RTF3-17 mm), side firing (SFT8-18 mm) and cylindrical (MGG6-6 mm). The following descriptive classification on surface damage was employed: no damage (class A), minimal effects (class B), metal fall with melting (class C), and destruction with carbonization (class D). The assessment was made through a descriptive scanning electron microscope (SEM) analysis. Side firing and conical tips at 50 mJ were classified as class A. Side firing at 84 mJ and cylindrical tips 50 mJ and 84 mJ were classified as class B. Finally, class C defects were found in the areas where the conical tip was used at 84 mJ. Side firing and conical tips at 50 mJ do not seem to damage the implant surface.